Competitive victimhood and reconciliation: the case of Turkish–Armenian relations. Issue 5 (2nd September 2020) - Demirel, Cagla; Eriksson, Johan
ABSTRACT: This paper argues that conflicts tend to be intractable if collective victimhood has become a component of national identity, and when conflicting communities claim to be the 'real' or 'only' victims, and that their suffering justifies crimes past and present. Turkish and Armenian narratives of competitive victimhood are analysed drawing on public opinion polls from Turkey and Armenia, and personal interviews with Turks and Armenians. The study corroborates past theory and research that competitive victimhood prevents reconciliation, particularly if it has become an essential part of national identity. The paper also shows that Turkish–Armenian relations remain at the bottom stage of the reconciliation ladder. Yet, some of our empirical observations suggest that when grass-roots level interaction between Turks and Armenians is facilitated (which has been prevented not least because of the closed border), there is room for the abandonment of competitive victimhood at least on an interpersonal level, if not on a general societal or political level.